1992
DOI: 10.1093/ajcp/98.6.637
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Platelets with Increased RNA Content (Reticulated Platelets) A Measure of the Rate of Thrombopoiesis

Abstract: Direct flow cytometric measurement of nucleic acid content in individual platelets is possible using the fluorescent dye Thiazole Orange (Becton-Dickinson, San Jose, CA). When applied to studies of thrombocytopenic patients, platelets with elevated nucleic acid content ("reticulated platelets") can be identified and quantitated. Labeling of these platelets is saturable and is abolished by treatment with RNAse. It has been suggested that, similar to the erythrocyte reticulocyte response to anemia, the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
249
2
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(266 citation statements)
references
References 0 publications
11
249
2
4
Order By: Relevance
“…Reticulated platelets were simultaneously counted via the method of Ault et al [34], with gating as shown in Figure 5C. Figure 1B shows that while the mean percentage of reticulated platelets (RP) is not elevated in WASP(−) mice, our colony contained a subpopulation of mice for which this parameter was elevated (p = 0.016, Student's one-tailed t-test for proportion of platelets with >8% reticulated forms).…”
Section: Platelet and Reticulated Platelet Counts By Quantitative Flomentioning
confidence: 98%
“…Reticulated platelets were simultaneously counted via the method of Ault et al [34], with gating as shown in Figure 5C. Figure 1B shows that while the mean percentage of reticulated platelets (RP) is not elevated in WASP(−) mice, our colony contained a subpopulation of mice for which this parameter was elevated (p = 0.016, Student's one-tailed t-test for proportion of platelets with >8% reticulated forms).…”
Section: Platelet and Reticulated Platelet Counts By Quantitative Flomentioning
confidence: 98%
“…For long it has been thought that this RNA was a vestigial remnant of megakaryocytic RNA, but there are recent indications that platelets are able using this RNA for protein synthesis [9]. Anyway, they represent the youngest platelets in the circulation and are named reticulated platelets (retPLT), in analogy with reticulocytes in erythropoiesis [10]. The concentration of retPLT in bone marrow is on the average 2-3 times higher than in peripheral blood, where they correlate with megakaryocyte numbers [11].…”
Section: Physiology Of Reticulated Plateletsmentioning
confidence: 99%
“…RP can be detected with thiazole orange (TO; Lee et al, 1986) staining combined with flow cytometric analysis of the fluorescence (FL; Kienast & Schmitz, 1990). The TO labelling has been shown to be sensitive to ribonuclease (RNAase), and thus may be considered to be due to an increased RNA content (Ault et al, 1992). …”
Section: Detection Of Reticulated Platelets (Rp)mentioning
confidence: 99%
“…Quantification of newly formed platelets would be useful and more easily adapted for clinical purposes and thus have advantages over platelet survival studies. In the circulation platelets with a high nucleic acid content, reticulated platelets (RP), have been thought to represent young platelets, and thus measurement of RP may give an estimate of megakaryocyte stimulation and platelet production (Ingram & Coopersmith, 1969;Kienast & Schmitz, 1990;Ault et al, 1992;Richards & Baglin, 1995).…”
Section: Introduction To Platelet Physiologymentioning
confidence: 99%